2023
DOI: 10.1001/jamainternmed.2022.6555
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Healthy Lifestyle Prior to Infection and Risk of Post–COVID-19 Condition

Abstract: ImportanceFew modifiable risk factors for post–COVID-19 condition (PCC) have been identified.ObjectiveTo investigate the association between healthy lifestyle factors prior to SARS-CoV-2 infection and risk of PCC.Design, Setting, and ParticipantsIn this prospective cohort study, 32 249 women in the Nurses’ Health Study II cohort reported preinfection lifestyle habits in 2015 and 2017. Healthy lifestyle factors included healthy body mass index (BMI, 18.5-24.9; calculated as weight in kilograms divided by height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 63 publications
6
30
0
2
Order By: Relevance
“…Our results were consistent with a recent study on a sample of female nurses that found an association between short sleep duration collected in 2017 and the occurrence of post-COVID-19 conditions. 44…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with a recent study on a sample of female nurses that found an association between short sleep duration collected in 2017 and the occurrence of post-COVID-19 conditions. 44…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, physical exercise-based rehabilitation resulted in limited adverse effects during routine clinical practice for some individuals who had had COVID-19. A major adverse event (i.e., increased dyspnea and exhaustion after training) was only reported during the first week of in-person training by a person who had been admitted to the intensive care unit during COVID-19 (59), whereas minor adverse events were observed in a small number of studies (51,59,61). Overall, physical exercise-based rehabilitation is generally considered safe and effective for individuals with long COVID; however, the severity of illness experienced by the patient during the infection should be seriously considered before the implementation of physical exercise-based rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of evidence-based treatments, prevention of long COVID is a key to reducing the overall burden of this condition. Both vaccination against SARS-CoV-2 and certain modifiable lifestyle factors are associated with lower risk of long COVID-19 ( Wang et al, 2023 ), and there is evidence that acute treatments including antivirals and metformin may be of benefit ( Carfì et al, 2020 ; Xu et al, 2020 ).…”
Section: Therapeuticsmentioning
confidence: 99%